Needle and thread - Martin, Ann M; Illustrations by Andreasen, Dan (London Scholastic Inc, 2007)
It's autumn in Camden Falls, and Flora and Ruby are just starting to settle into the town. Flora is worried about spending the first Thanksgiving without their parents. Ruby is worried about getting a part in her school musical. And their new friends, Olivia and Nikki, are facing problems of their own. But the friendship that ties them together will also give them the strength to work things out -- one stitch at a time.
Keywords: Thanksgiving Day -- New England -- Female friendship